ANALISIS.KERAPATAN JALAN HUTAN BERDASARKAN HASILPENAFSIRAN FOTO UDARA DAN SURVEl LAPANGAN: STUDI KASUS PT.INHUTANI II - Ishak Sumantri (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
Forest road network has a very important role in tranaporling logs fram the frest to processing site or logyard. The investigation of forest road density by using theaerial photo of l : 20.000 and 1: 60.000 scales had been conducted.The scope of the aerial photo is the second five-year working plan of PT. lnhutani 11 Pulau Laut, South kelimanten. The results are. as follows :1.Based on aerial photo interpretation, forest road density is 7,6 m/ha.2.Based on average skidding distance, and road construction and road maintenance costs, road denvities ha and 17,4 m/ha. respectively.3. Actual forest road density in PT. lnhutani II forest area is not optimum yet because it is far less than optimum values resulted from calculation based on average skidding distance and road construction and maintenance costs.